Evaluation of Root Perforation Treatments with Mineral Trioxide Aggregate: A Retrospective Case Series Study - Melo, Pedro Henrique Alves de; Machado, André Guimarães; Machado, André Luiz Barbosa; Carvalho, Flávio Narciso; Melo, João Bastista de; Schneider, Luis Felipe Jochims (Iranian Endodontic Journal, 2019)
This study aimed to evaluate the long-term clinical success of the use of mineral trioxide aggregate (MTA) as root canal sealer in root perforation treatments. Therefore, the dental records of 53 patients were analyzed, and treatment data was collected (age, gender, tooth location, jaw, presence or absence of radiolucent lesion, fallow up time and final radiographic/clinical assessment). All procedures were performed by a single specialist. Two examiners analyzed three radiographs from the records of each patient and classified the treatments as successful or unsuccessful. Data was analyzed statistically using parametric chi-square (P≤0.05). The examiners classified 69.8% of the cases as successful, with a follow-up time of 1-16.25 years (average: 6 years). The presence of initial radiolucent lesion was observed in 79.2% of the teeth, with a higher index of treatment in maxillary teeth (62.3%). However, the majority of successful cases were located in the maxilla (73.0%), while most unsuccessful ones were located in the mandible (62.5%) (P=0.014). There was no statistically significant difference regarding presence of previous lesions in successful (75.7%) and unsuccessful cases (87.5%) (P=0.330). In the present study, root perforations sealed with MTA had a success rate of 69.8% within 1-16.25 years. The presence of initial injury did not influence the prognosis, and maxillary teeth presented a higher success rate. Keywords: Mineral Trioxide Aggregate; Perforation; Endodontics